Clinicopathologic Characteristics of Endometrial Cancer in Lynch Syndrome: A French Multicenter Study. Issue 5 (June 2017) - Rossi, Léa; Le Frere-Belda, Marie-Aude; Laurent-Puig, Pierre; Buecher, Bruno; De Pauw, Antoine; Stoppa-Lyonnet, Dominique; Canlorbe, Geoffroy; Caron, Olivier; Borghese, Bruno; Colas, Chrystelle; Delhomelle, Hélène; Chabbert-Buffet, Nathalie; et al.
Abstract : Background: Limited data exist on Lynch syndrome (LS)–related endometrial cancer (EC) features. Amsterdam criteria II, commonly used, have poor sensitivity for detection of LS, which is underdiagnosed. Aim: The aim of this study was to describe the clinical and pathological features of LS-related EC among mutation-proven patients. Methods: We conducted a retrospective study from 1977 to 2013 in 5 hospitals. The inclusion criteria were patients who had a primary EC associated to LS proven by a germline mutation. We analyzed the clinical data and the pathology of the tumors. The patient management and the survival data were also collected. Results: Forty-nine patients (15 MLH1, 20 MSH2, 13 MSH6, 1 PMS2 ) were included. The mean age at diagnosis was 49.7 (SD, 10.5) years. The median body mass index was 22.6 kg/m 2 . In 81.4% of cases, EC was the first cancer of the LS spectrum to occur. Endometrioid adenocarcinoma accounted for 89.2% of the EC, the lower uterine segment was involved in 25% of cases, and a synchronous ovarian cancer was present in 21.6% of patients. The tumors were grade 3 in 19.3% of cases and FIGO (International Federation of Gynecology and Obstetrics) stage I in 66.6% of cases. With a median follow-up of 58 months, 3 patients with conservative management developed a recurrence, and no patient died of EC. Conclusions: The LS-associated EC is characterized by a young age at onset, a high prevalence of lower uterine segment involvement, and synchronous ovarian cancers. The prognosis of these cancers does not appear different from sporadic tumors.